Hydro-elastic modelling of an electro-active wave energy converter - Babarit, Aurélien; Benjamin, Gendron; Singh, Jitendra; Mélis, Cécile; Jean, Philippe (Volume 9: Odd M. Faltinsen Honoring Symposium on Marine Hydrodynamics, 2013)
ASME 2013 32nd International Conference on Ocean, Offshore and Arctic EngineeringVolume 9: Odd M. Faltinsen Honoring Symposium on Marine HydrodynamicsNantes, France, June 9–14, 2013Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-5543-0 International audience Since 2009, SBM Offshore has been developing the S3 Wave Energy Converter (S3 WEC). It consists in a long flexible tube made of an Electro-Active Polymer (EAP). Thus, the structural material is also the Power Take Off (PTO). In order to optimize the S3 WEC, a hydro-elastic numerical model able to predict the device dynamic response has been developed. The inner flow, elastic wall deformations and outer flow are taken into account in the model under the following assumptions: Euler equation is used for the inner flow. The flow is also assumed to be uniform. Elastic deformation of the wall tube is linearized. The outer flow is modeled using linear potential theory. These equations have been combined in order to build the numerical model. First, they are solved in the absence of the outer fluid in order to obtain the modes of response of the device. Secondly, the outer fluid is taken into account and the equation of motion is solved by making use of modal expansion. Meanwhile, experimental validation tests were conducted in the ocean basin at Ecole Centrale De Nantes. The scale model is 10m long tube made of EAP. The tube deformations were measured using the electro-active polymer. The model was also equipped with sensors in order to measure the inner pressure. Comparisons of the deformation rate between the numerical model and experimental results show good agreement, provided that the wall damping is calibrated.Eventually, results of a technico-economical parametric study of the dimensions of the device are presented.